Wind vibration control of stay cables using magnetorheological dampers under optimal equivalent control algorithm. (17th March 2019) - Zhao, Yu-Liang; Xu, Zhao-Dong; Wang, Cheng
Abstract: In a cable-stayed bridge, the employment of magnetorheological (MR) dampers among stay cables are steadily increasing for mitigation of rain-wind induced vibration. A major problem for the practical application of these devices is to develop a suitable algorithm that effectively suppresses the vibration of stay cables with basic calculations and minimal feedback requirement. This paper discusses an optimal equivalent control algorithm for vibration mitigation of stay cables based on the linear quadratic regulator (LQR). The control algorithm is anticipated to effectively reduce the risk of structural response amplification, which is due to the control forces along the direction of MR damper motion. Furthermore, this algorithm approximates the optimal LQR control forces through equivalent stiffness and damping, resulting in a significant reduction in the calculative effort of the optimal control forces. Hence, it is proved as a great significance for the MR semi-active control system application in the field of practical engineering. In the proposed equivalent control technique, control performance is evaluated by the vibration control problem faced by wind induced stay cable of the Second Nanjing Yangtze River Bridge. The results demonstrate that the MR semi-active control algorithm as proposed in this paper performs better than that of optimal passive control with almost achieving the level of LQR control with minimal feedbacks requirements.